The Farming Land Tenure by Corporation: People’s Economic Rights Protection Perspective - Budijanto, Budijanto (International Journal of Social and Local Economic Governance, 2015)
The purpose of this study was to describe the various conditions that  background household workers who are motivated to migrate internasioanal; sending remittances to their home town and the impact of migration international TKI on social, economic, and  culture  in the area of origin. The approach of the research is quantitative approach., collecting data with interview techniques. and. indept interview / in-depth interviews to sharpen and enrich the information phenomenon sosial.Analisis data with descriptive analysis and paertial laest square.The results showed an increase in production efficiency with a shorter time, production capacity and product quality improved so that it can meet consumer demand. The purpose of this study was to describe the various conditions that  background household workers who are motivated to migrate internasioanal; sending remittances to their home town and the impact of migration international TKI on social, economic, and  culture  in the area of origin. The approach of the research is quantitative approach., collecting data with interview techniques. and. indept interview / in-depth interviews to sharpen and enrich the information phenomenon sosial.Analisis data with descriptive analysis and paertial laest square.Keywords: international migration, migrant workers, utilization, of origin remittance.